Pendampingan Prinsip FITT pada Olahraga bagi Guru PKG-PAUD Kecamatan Bojongsoang Kabupaten Bandung - Sajodin Sajodin; Perla Yualita (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Sport is an activity carried out systematically to improve physical and spiritual health. Exercise is also like a double-edged sword; on the one hand, exercise can improve health and avoid various diseases, but on the other hand, exercise can also cause injury if not done properly. Especially in early childhood, those who play sports can pose a danger to themselves, so the role of the teacher is vital in directing sports to early childhood children. The FITT principle (Frequency, Intensity, Type, and Time) is one of the principles that teachers can use to direct sports in early childhood correctly. The purpose of this PkM is to increase teacher knowledge to apply the FITT principle in sports at PKG-PAUD, Bojongsoang District, Bandung Regency. The method of implementing this activity goes through four stages firstly; a situation analysis is carried out on activity partners; secondly, a pretest is carried out by measuring the teacher's knowledge of the FITT principle in sports; the third is providing sports material and practice to children using the FITT principle, fourth at the end of the activity, post-test and activity evaluation are carried out. The results of this PkM show an increase in teacher knowledge about the FITT principle by 89.43%. Thus, in general, teachers have developed sports training programs for early childhood using the FITT principle.